Analytical Model of the Piezoresistive Behavior of Highly Compressible Sensors Made of Microporous Nanocomposites. Issue 12 (18th October 2021) - Zhang, Jianpeng; Wang, Ziya; Peng, Zhengchun
Abstract: Microporous conductive nanocomposites, compared with conventional filler‐matrix composites, enable flexible piezoresistive sensors with higher sensitivity and a larger measurement range. Previous research focuses on different methods of fabricating porous materials that are highly sensitive to pressure, however, there is only a small amount of research studying the mechanism of those sensors. Without an appropriate theoretical guide, relying on expensive experimental approaches to enhance the sensitivity will significantly limit the advancement of this technology. This article proposes an efficient analytical model, with some parameters determined from experiments, to investigate the piezoresistive behaviors of microporous nanocomposites. The predicted results agree well with the analysis from finite element models as well as the experimental data. Moreover, scaling law is applied to study the effect of geometry, material, and interface on the sensitivity of the sensor. This study establishes the theoretical foundation for the design of a high‐performance piezoresistive sensor based on microporous nanocomposites. Abstract : This article proposes an efficient analytical model, with some parameters determined from experiments, to investigate the piezoresistive behaviors of microporous nanocomposites. The predicted results agree well with the analysis from finite element models as well as the experimental data. This study establishes the theoretical foundation for the design of a high‐performance piezoresistive sensor based on microporous nanocomposites.